Jurnal HUBUNGAN DUKUNGAN SOSIAL DENGAN KUALITAS HIDUP LANSIA PADA PENDERITA DIABETES MELITUS DI RUMAH SAKIT UMUM SEMBIRING DELI TUA TAHUN 2025 - Purba, Rentawati; Barus, Dewi Tiansa (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2025)
Social assistance is crucial for enhancing older people's quality of life, especially for those suffering from diabetes mellitus (DM). Elderly people with DM often face challenges both physically and emotionally, so social support from family, friends or other social groups can enhance their standard of living. This research It wants to examine the connection between senior citizens' quality of life and social support with diabetes mellitus at Sembiring General Hospital Deli Tua. This kind of study uses a cross-sectional methodology and is correlational.The population and sample were 68 respondents, samples were taken using purposive sampling. The instrument uses a standard questionnaire. Statistical analysis uses chi square. The findings of the study indicate a connection between senior citizens' quality of life and social assistance (p-value 0.007). In conclusion, Social support and the quality of life of older adults with diabetes mellitus are related at Sembiring General Hospital Deli Tua. It is anticipated that this study will input to provide education about the association between senior citizens' quality of life and social support in diabetes mellitus patients so believe it will have a greater effect in the future on health.